A Short History of Medicine - Ackerknecht, Erwin H. (Erwin Heinz), 1906-1988 (Book collections on Project MUSE., 2016)
Erwin H. Ackerknecht?s A Short History of Medicine is a concise narrative, long appreciated by students in the history of medicine, medical students, historians, and medical professionals as well as all those seeking to understand the history of medicine. Covering the broad sweep of discoveries from parasitic worms to bacilli and x-rays, and highlighting physicians and scientists from Hippocrates and Galen to Pasteur, Koch, and Roentgen, Ackerknecht narrates Western and Eastern civilization?s work at identifying and curing disease. He follows these discoveries from the library to the bedside, hospital, and laboratory, illuminating how basic biological sciences interacted with clinical practice over time. But his story is more than one of laudable scientific and therapeutic achievement. Ackerknecht also points toward the social, ecological, economic, and political conditions that shape the incidence of disease. Improvements in health, Ackerknecht argues, depend on more than laboratory knowledge: they also require that we improve the lives of ordinary men and women by altering social conditions such as poverty and hunger. This revised and expanded edition includes a new foreword and concluding biographical essay by Charles E. Rosenberg, Ackerknecht?s former student and a distinguished historian of medicine. A new bibliographic essay by Lisa Haushofer explores recent scholarship in the history of medicine.